Investigating the concept of representation in the neural and psychological sciences - Favela, Luis H.; Machery, Edouard (Frontiers in Psychology, 2023)
The concept of representation is commonly treated as indispensable to research on brains, behavior, and cognition. Nevertheless, systematic evidence about the ways the concept is applied remains scarce. We present the results of an experiment aimed at elucidating what researchers mean by “representation.” Participants were an international group of psychologists, neuroscientists, and philosophers (N = 736). Applying elicitation methodology, participants responded to a survey with experimental scenarios aimed at invoking applications of “representation” and five other ways of describing how the brain responds to stimuli. While we find little disciplinary variation in the application of “representation” and other expressions (e.g., “about” and “carry information”), the results suggest that researchers exhibit uncertainty about what sorts of brain activity involve representations or not; they also prefer non-representational, causal characterizations of the brain’s response to stimuli. Potential consequences of these findings are explored, such as reforming or eliminating the concept of representation from use.